The Impact of Teachers’ Attitudes on Students’ English Speaking Anxiety In The Context of Kerala - Som Nepali (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This is a qualitative research study that descriptively discovered the effects of teachers’ attitudes on students’ English speaking anxiety, which was being addressed by determining the teachers’ attitudes towards students in terms of their English speaking performance and English speaking anxiety, and students’ feelings about their teachers’ attitudes during their English speaking performance. An interview questionnaire comprised of open-ended questions was utilized to interview the 15 student and 6 teacher participants of this study, who are currently connected from the two prestigious universities in Kerala. The interview findings revealed the following effects of instructors' attitudes on students' English speaking anxiety: Teachers' student-friendly approach and interactive instructional strategies can alleviate students' English speaking anxiety, and teachers as stern and firm monitors of students' language use make students more aware of themselves, which drives them to be extensively scared of committing mistakes and not meeting their teachers’ expectations. Out from the gathered verbal data and results, this study concluded that teachers are indeed major determinants of students’ English speaking anxiety. Teachers' shown behavioural and instructional attitudes have a major role in increasing students' anxiety and apprehension in utilising the target language orally, which has an impact on their English speaking performance.